2022
DOI: 10.3389/fgene.2022.911010
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of COVID-19 Outcomes Reveals Novel Host Genetic Risk Loci in the Serbian Population

Abstract: Host genetics, an important contributor to the COVID-19 clinical susceptibility and severity, currently is the focus of multiple genome-wide association studies (GWAS) in populations affected by the pandemic. This is the first study from Serbia that performed a GWAS of COVID-19 outcomes to identify genetic risk markers of disease severity. A group of 128 hospitalized COVID-19 patients from the Serbian population was enrolled in the study. We conducted a GWAS comparing (1) patients with pneumonia (n = 80) again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…Several human GWAS studies have identified host genes and genetic loci associated with variation in SARS-CoV-2 disease severity and long-COVID [ 37 , 38 , 39 , 57 , 58 , 59 , 60 , 61 , 62 ]. Analysis of the impact of host genetic variation on SARS-CoV-2 vaccine-induced immunity has found associations between variant HLA alleles and variation in vaccine-induced antibody responses, vaccine breakthrough and vaccine side effects [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several human GWAS studies have identified host genes and genetic loci associated with variation in SARS-CoV-2 disease severity and long-COVID [ 37 , 38 , 39 , 57 , 58 , 59 , 60 , 61 , 62 ]. Analysis of the impact of host genetic variation on SARS-CoV-2 vaccine-induced immunity has found associations between variant HLA alleles and variation in vaccine-induced antibody responses, vaccine breakthrough and vaccine side effects [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include old age, comorbidities, smoking, and low socioeconomic status. In addition, more than 20 loci throughout the genome have been associated with COVID-19 phenotypes in genome-wide association studies (GWAS) [1,2,3]. Big consortia, such as the Host Genetic Initiative (HGI) and UK Biobank (UKBB), analyzed data of thousands of patients with COVID-19 and healthy individuals to assess genetic factors predictive of infection vulnerability, hospitalization and severe disease [1,2].…”
Section: Genetics and Coronavirus Disease 2019mentioning
confidence: 99%
“…Najsavremenija genetička ispitivanja obolelih od kovida sprovode se u mnogim zemljama, a nedavno su sprovedena i u srpskoj populaciji kod obolelih od kovida koji su hospitalno lečeni. Dobijeni rezultati sugerišu da postoje genetički markeri koji su jasni indikatori težih oblika bolesti, pre svega, težih kovid pneumonija, što se značajnim delom ogleda i u postkovid posledicama (18).…”
Section: Postkovid I Respiratorne Manifestacijeunclassified